1996
DOI: 10.1074/jbc.271.15.8700
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of the Vitamin D Analog, 22-Oxacalcitriol, Using Cultured Osteosarcoma, Hepatoma, and Keratinocyte Cell Lines

Abstract: 1 has potent cell differentiating/anti-proliferative activities in addition to its role in calcium homeostasis (1). This has led researchers in both universities and the pharmaceutical industry to search for so-called "noncalcemic" vitamin D analogs with accentuated differentiating/anti-proliferative properties and reduced ability to cause hypercalcemia (2, 3). 22-Oxacalcitriol (OCT) 2 was an early analog developed for this purpose and contains a 22-oxygen atom that replaces the 22-carbon of calcitriol. OCT bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…At this concentration we did not find accumulation of more polar metabolites as we have seen in many previous studies which employed higher (10 µ M ) concentrations [30, 31]. The recovery of metabolites during the extraction procedure was >90% for all samples (data not shown).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…At this concentration we did not find accumulation of more polar metabolites as we have seen in many previous studies which employed higher (10 µ M ) concentrations [30, 31]. The recovery of metabolites during the extraction procedure was >90% for all samples (data not shown).…”
Section: Resultssupporting
confidence: 81%
“…The base peak at m/z 131 is indicative of an intact C25-hydroxyl group and absent if either C26 or C27 has occurred, and our previous studies have shown that the m/z 131 peak is more intense, relative to the other ion species, when 24-hydroxylation has occurred. Although there was insufficient material to perform further chemical characterisation the spectrum mirrors precisely that of authentic 24-hydroxy-OCT as we have previously published [30]. …”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Upon LC/MS analysis (data not shown), we observed the disappearance of M2, but not M1 or M3 (both 23-hydroxylated) or the substrate, 1,25(OH) 2 D 3 . In the second experiment, purified M2 was esterified with n-butylboronic acid, which produces a cyclic boronate from a molecule that possesses vicinal hydroxyl groups (Masuda et al, 1996) and was then derivatized with BSTFA plus 1% TMCS. Its mass spectrum after GC/MS (Fig.…”
Section: Metabolism Of 125(oh) 2 D 3 By Human Liver and Small Intestmentioning
confidence: 99%
“…Coexpression plasmids for CYP24, adrenodoxin, and adrenodoxin reductase were reported previously (pKSNdl-CYP24) (25). Recombinant Escherichia coli cells transfected with the above plasmids (JM109/ pKSNdl-CYP27B1 or JM109/pKSNdl-CYP24) were grown in TB medium (26) 70,000) in 3.5 mM barbiturate buffer (pH 8.6) containing 0.13 M NaCl and 0.1% ovalbumin was measured following the addition of the compounds as described previously (16,20,27).…”
mentioning
confidence: 99%